DEVELOPING STUDENTS' ECOLOGICAL COMPETENCE THROUGH INDEPENDENT LEARNING ACTIVITIES - Safarova Nilufar Mirzakulovna (Journals Park Publishing, 2024)
"Enhancing Students' Ecological Competence through Independent Learning Activities" emphasizes the importance of shaping students' ecological competence through independent learning activities. The article highlights the potential increase in students' ecological competence, likely fostering environmental awareness and responsibility among them. The term "ecological competence" is discussed in the context of effectively engaging with environmental issues through essential knowledge, skills, and attitudes. Various methods and strategies for developing independent learning in the context of ecological education are discussed in the article, addressing issues of practical experience, integrating environmental topics into the curriculum, and considering the challenges of incorporating environmental concerns into education. The goal is to instill in students the initiative and responsibility to preserve the environment, contributing to a sustainable and environmentally conscious future.
Keywords: competence, ecological competence, environmental sustainability, integration, excursion, online platform, virtual environment, mentoring, surroundings, educational integration.